019 Optimisation of imaging orders in intensive care units. (23rd September 2015) - Lehot, Jean-Jacques; Revel, Didier; Douek, Philippe; Catherine, Heuclin; Desgranges, François-Pierrick; Neidecker, Jean
Abstract : Background and objectives: X-rays account for a large fraction of intensive care unit (ICU) costs. Unnecessary orders pointlessly increase the workload of technicians and lead to unnecessary exposure of patients to radiation. The underlying reason for the order is often a fear of a missed diagnosis. No account is taken of the advances made in bedside echography. We undertook a feasibility study in a postoperative acute care unit in cardiovascular and thoracic surgery, in order to evaluate whether intensivists would agree to reducing x-ray orders and to assess the consequences of such a policy on patient outcomes. Programme: The programme started on 21 December 2006, with two to three staff meetings a year in order to analyse prescriptions for bedside x-rays and TDM. The analysis was performed by consultants, residents and registrars (intensivists, radiologists). The radiologists presented the findings at each meeting. Systematic orders were discouraged and targeted orders were encouraged. Systematic bedside X-rays after central catheter insertion were kept for reasons of safety. Nurses were told not to ask for bedside X-rays that had not been ordered by a physician. All new residents were informed about the programme and were trained in thoracic ultrasound scanning. Progress was also monitored during monthly morbidity-mortality meetings. Results: 2006 2007 2008 Number of open beds (mean) 28.8 27.6 27.3 Number of patients 1728 1754 1813 Mean age of patients (yr) 53.3 52.8 59.7 Total production of ICU (RCI) 2643181 2544141 2733860 Bedside X-rays (RCI) 267529 249638 241457 Number of TDM 516 473 429 RCI, Relative Complexity Index. Discussion and conclusion: Despite the increase in activity and in mean patient age, bedside X-rays decreased by 10% and bedside TDM by 16.8%, leading to a reduction in patient exposure to radiation and in staff workload. No increase in morbidity, mortality and potentially avoidable deaths was observed. The use of thoracic ultrasound scanning for pulmonary and pleural imaging however increased and proved to be a valuable tool. For this trend to continue, it is essential that physicians be able to share their experience and that students and registrars be taught better targeting of medical orders. Contexte: Les examens d'imagerie représentent une part importante des dépenses des services de réanimation. Or, la surprescription induit un surcroît de travail pour les manipulateurs d'électroradiologie et une irradiation inutile des patients. Ces prescriptions sont habituellement justifiées par la crainte de méconnaître une pathologie. Cependant, cette habitude ne tient pas compte du développement de l'échographie thoracique. Une étude de faisabilité a été menée dans un centre de responsabilité (CR) de réanimation post-chirurgie cardiovasculaire et thoracique afin de savoir si des réanimateurs hospitaliers accepteraient une telle politique et si cette dernière avait des conséquences sur la qualité des soins. Programme: Ce programme a été initié le 21 décembre 2006 avec deux à trois réunions annuelles de concertation portant sur les actes d'imagerie. Les responsables du service de radiologie participaient à ces réunions afin d'étayer la démarche et d'en suivre les effets sur le volume des prescriptions. Il était demandé aux médecins de ne pas prescrire de radiographie au lit sans motivation et aux infirmiers de ne pas demander d'examen non prescrit. A chaque début de semestre, une information était donnée aux nouveaux internes. Parallèlement, une réunion mensuelle de morbi-mortalité permettait de monitorer les effets de cette politique. Résultats: L'activité et les résultats médico-économiques du CR sont résumés dans le tableau: Année 2006 2007 2008 Nombre moyen de lits en service 28.8 27.6 27.3 Nombre de patients admis 1728 1754 1813 Age moyen (ans) 53.3 52.8 59.7 Production totale (ICR) 2643181 2544141 2733860 Radiographies (ICR) 267529 249638 241457 Nombre de TDM 516 473 429 Discussion: En dépit d'une augmentation de l'activité et de l'âge des patients, la consommation d'actes d'imagerie dans le CR a diminué de 10% concernant les radiographies au lit et de 16, 8% concernant les tomodensitométries. Ceci a permis de diminuer l'irradiation des patients et de réduire la charge de travail des manipulateurs d'électroradiologie. Parallèlement, il n'a pas été mis en évidence d'augmentation de morbi-mortalité et de décès potentiellement évitables. Par contre, les échographies thoraciques examinant les plèvres et le parenchyme pulmonaire se sont développées, permettant ainsi un meilleur apprentissage des internes.